Strengthening the Party’s leadership to realize Vietnam’s aspiration 2045 - Anh, Dr Nguyen Ngoc (The journal of contemporary issues in business and government, 2021)
As the leading force of the country and society (Article 4, Constitution 2013), the Communist Party of Vietnam (CPV)set strategic direction and strategies for the country’s important issues including socio-economic development, foreign affairs and national defence… and oversees the implementation process. The Vietnam’s aspiration to become a developing country with modern industry, upper middle-income level by 20302and a developed country with high income level by 20452is highly ambitious. It was stated in thecountry’s socio-economic development strategy for period 2021-2030, which has been adopted by the Party’s Congress XIII. Realization of this aspiration would require strong Party’s leadership, State’s good management capacity and active contribution from businesses and people. The Party’s strong leadership is a prerequisite for success in the Vietnamese context. It is therefore important to strengthen the Party’s leadership to realize this high aspiration.